(untitled) (Journal of the College of Basic Education, 2022)
The research included five sections: The First Section: Define the research and its importance and forming> The research aimed at knowing the relationship between concentrate attention and its relation with accuracy of dispatching for disabled from state of sitting for Wesam Al-Mahjed team in Baghdad. Research Assumption: there is a relation with connected statiscal reference between concentrate attention and its relation with accuracy of dispatching for disabled from state of sitting. The Second Section: this section included the similar and theoretical studies and described the attention and concentrate the attention types of attention nature of attention process and factors that effected on attention the individual differences in attention also accuracy and its types. The third section: Procedures of research, this research contained the approach of research and the used tools and statistical means the fourth Section: Presentation the result and discussing it and by them we reached to achieving the purposes. The fifth Section : conclusions and recommendations This section included the conclusion the research researched to it through his study and the most important are: 1-Existence connected relation with moral sign between concentrate attention and the accuracy of dispatching 2- There was high concentrate attention and also accuravy in kill of dispatching. Most important recommendations are: 1- Doing similar research in elation with concentrate attention and accuracy of dispatching and other attack skills. 2- Giving enough time during perform skill in order to do it in the right way.